The level of independence of children with intellectual disabilities in maintaining dental and oral hygiene at home: A literature review - Siahaan, Joni; Setiawan, Yana; Harissya, Zulaika; Pohan, Dessy Syahfitri; Estiadewi, Primalova Septiavy; Nurshadrina, Kharina; Hernando, Zahfia Nadzwa Clarisa (Science Center Group, 2025)
Background: Limitations in cognitive and motor skills make these children more dependent on external support, particularly from their families. Family involvement is therefore considered an important factor in promoting independence and improving oral hygiene behaviors among children with intellectual disabilities. Objective: This study aimed to analyze the relationship between family support and the level of independence of children with intellectual disabilities in maintaining dental and oral hygiene at home. Methods: This study employed a literature review design following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. A systematic search was conducted in several scientific databases, including Google Scholar, ScienceDirect, and PubMed, using combinations of keywords related to family support, oral hygiene, intellectual disability, and children with special needs. Articles published between 2020 and 2025 were screened based on predefined inclusion and exclusion criteria. The quality of the selected studies was evaluated using the Critical Appraisal Skills Programme (CASP) tool. Results: Ten studies met the inclusion criteria and were included in the analysis. The findings consistently indicated a strong positive relationship between family involvement and the oral hygiene status of children with intellectual disabilities. Parental education, supervision, and training programs were shown to significantly improve children’s tooth-brushing behavior, reduce plaque accumulation, and enhance oral hygiene practices at home. However, several barriers were identified, including limited parental knowledge, inadequate supervision, and the motor and behavioral limitations experienced by children with intellectual disabilities. Conclusion: Family support plays a crucial role in improving the independence of children with intellectual disabilities in maintaining dental and oral hygiene at home. Strengthening family-based education, parental training, and supportive home-care interventions may enhance oral health outcomes and improve the overall quality of life of children with intellectual disabilities.